EFEKTIVITAS PENERAPAN ATURAN PONDOK DALAM PEMBENTUKAN AKHLAKUL KARIMAH SANTRI DI PONDOK PESANTREN - Megawati; Hardianto Rahman; Mustamir (Jurnal Al-Ilmi: Jurnal Riset Pendidikan Islam, 2022)
This study aims to see the Effectiveness of the Application of Pondok Rules in Formation of Akhlakul Karimah Santri at the Darul Istiqamah Bongki Islamic Boarding School, Kec. North Sinjai Kab. Sinjai. This research is included in the type of evaluation research using a quantitative approach. The subjects of this study were students of MTs and MA Pondok Pesantren Putri Darul Istiqamah Bongki. The data collection method is by distributing questionnaires (questionnaires), making observations, and collecting information from sources or available documents. The results showed that the effectiveness of the application of the rules of the boarding school had a significant effect on the formation of the morality of the santri of the Putri Darul Istiqamah Bongki Islamic Boarding School where the effectiveness level was 81.5%. In the application of the rules at the Darul Istiqamah Bongki Islamic Boarding School, there is a reciprocal process and dynamic interaction between students, teachers, and the pesantren environment in general. The teacher is a role model and the environment is the shaper of conditions and comfort, as well as the climate of the boarding school to develop good morality for the students. The synergy of all these elements will certainly return to the students as individuals who are in a very dynamic environment.